INTERACTIVE TEACHING METHODS AT HIGHER EDUCATIONAL INSTITUTIONS - Usmanaliev Khusniddin (Nurul Jadid University, 2018)
This article is devoted to the benefits of the modern methods of interactive teaching in higher educational institutions. Because these methods motivate students to gain more knowledge and inspire them to have interest in their work. Besides, the methods provide the students with feeling of self-confidence and freedom of expression of their mind. Further, the list of the most modern and widespread teaching methods will be provided which may have possible potentials for the future specialists and professionals.